ETHNOLOGICAL RESEARCH: THE CASE OF UZBEKS IN SOUTH KOREA - Rahimberdiyev Sardorbek Bekmurod ugli (American Journals Publishing, 2024)
South Korea is considered one of the most developed countries in the world, it was one of the first to recognize the independence of Uzbekistan (1991), and it is one of the closest partners. Since the 1990s, high indicators of economic growth have been recorded in this country. Most of the local population did not want to do jobs that were considered to be relatively low-paid. Due to these reasons, the government began to attract workers from abroad. Due to these attractive offers, many of our compatriots went to the Republic of South Korea. Therefore, this article discusses the life and lifestyle of Uzbeks living in South Korea in detail. Also, information is given about the reasons and goals of the Uzbeks living as emigrants to go abroad. Special methods of overcoming the difficulties faced by foreigners, differences in cultures and customs are also highlighted.
Keywords: Republic of South Korea, international labor market, unemployment, population growth, international economic relations, economic development, culture shock, marriage migration, student, immigrant, migration, immigration, koryo-in, koryo saram, deportation, vacancy, UN, cultural center, culture shock, demographic decline, investor.